Migration timing, return patterns, and tradeoffs for the early life stage of tributary spawning flannelmouth sucker (Catostomus latipinnis) - Bonjour, Sophia Marie (Kansas State University, 2024)
Tributary streams can be important aspects of temporal and spatial heterogeneity in river networks impacted by anthropogenic activities. Tributaries are critical in the life history of some species and may be essential to support large-river fish populations through portfolio effects, whereby multiple spawning locations increase recruitment success. Migration timing, site fidelity, and the experience for offspring within tributaries can have population-level impacts throughout river networks. I examined how flannelmouth sucker, Catostomus latipinnis, use tributaries for spawning and the implications for larvae and juveniles hatched in these systems. In Chapter 2, I evaluated the relationship between the timing and duration of sucker migration and environmental cues across four tributaries in the Colorado River basin. For the San Juan River, I also quantified the use of a tributary, McElmo Creek, based on the proximity of fish to the tributary and movement in the mainstem prior to and following spawning. More than half of the fish tagged within 10 km of McElmo Creek spawned in the tributary the following spring with decreased use by fish tagged farther from the confluence. Fish staged at the mouth of McElmo Creek an average of 8 days before entering the tributary, coming from both upstream and downstream. Arrival and residence times varied across years with greater discharge, across years or sites, associated with extended tributary use. This suggests conservation actions prioritizing a natural flow regime, connectivity, and limited water extraction may benefit migrating fish, including flannelmouth sucker. In Chapter 3, I created detection histories from long-term passive integrated transponder (PIT) data to assess the site fidelity of spawning flannelmouth sucker to McElmo Creek. Encounter rates of PIT-tagged fish and apparent survival exhibited interannual variation and were dependent upon length at tagging. Annual site fidelity was generally high, averaging 0.93 across years and ranging from 0.80 to 0.98, which may benefit individuals by minimizing energetic costs associated with habitat exploration and selection but may be maladaptive in systems with rapid anthropogenic changes. Individual fish demonstrated consistency in relative arrival timing across years with stronger relationships in years with longer spawning seasons. Partial migration and separation of migration timing may act as two forms of bet-hedging in dynamic systems. In Chapter 4, I examined the differences in early life history sucker experiences based on spawning location by conducting an enclosure experiment in combination with observational data. Whether juvenile fish grew more in the mainstem or tributary depended upon year and environmental conditions. Spawning occurred earlier in the tributary than the mainstem in 2022 and 2023, which could lead to a competitive advantage against individuals with shorter growing times. However, suckers grew more in mainstem enclosures in 2023, perhaps due to negative effects of abundant non-native crayfish at tributary sites. Differences in experience during early life stages between tributary and mainstem habitats, and among years support the idea that tributary spawning acts as a population-level bet-hedging strategy that may contribute to the persistence of flannelmouth sucker where other native species are threatened or endangered. This work contributes to our understanding of the movement and reproductive ecology of flannelmouth sucker and the role of tributaries in their life history. Conservation or degradation of tributary attributes, such as connectivity, flow and temperature regimes, and larval habitat, will impact the resilience of native fishes, including flannelmouth sucker.
Keywords: Fish ecology; Movement; Colorado River basin; Telemetry; Conservation; River network